Synthesis of MoO3 by pilot‐scale combustion reaction and evaluation in biodiesel production from residual oil. (24th January 2022) - da Silva, Adriano Lima; Farias, Ana Flávia Felix; da Costa Agra de Melo, João Baptista; Rodrigues, Alisson Mendes; Meneghetti, Simoni Margareti Plentz; de Melo Costa, Ana Cristina Figueiredo
Summary: The MoO3 was synthesized on a pilot scale by combustion reaction and their catalytic performance was investigated to obtain biodiesel from residual oil by simultaneous reactions of transesterification and esterification (TES). The catalyst was characterized by X‐ray diffraction with respective Rietveld refinement, Fourier transform infrared, and RAMAN spectroscopies, scanning electron microscopy, determination of the specific surface area by the method of N2 adsorption (Brunauer, Emmett, and Teller), and acidity test by temperature‐programmed desorption of ammonia molecule. The catalytic properties were evaluated through catalytic tests while the products of the TES reactions were characterized by gas chromatography, kinematic viscosity, and acidity index. Such results indicated that single‐phase catalysts (α‐MoO3 ‐100%) and biphasic ( h /α‐MoO3 ‐hexagonal 56.80% and orthorhombic 43.20%) were synthesized, which presented crystalline fraction and crystal size of 88% to 90% and 33 to 84 nm, respectively. The crystalline phases (α‐MoO3 and h/α‐MoO3 ) showed typical morphologies of microplate agglomerates, irregular rods, the surface area of 1.5 to 4.7 m 2 g −1, and total acidity equivalent to 30 to 84 μmol g −1 NH3 . The MoO3 was successfully synthesized by pilot‐scale combustion reaction and showed promising results, with high conversions to ethyl esters (between 93% and 99%), maintaining activity (useful life) after five consecutive reuse cycles. Thus, the catalysts studied have the potential to enable positive impacts on the environment and society in general.